Multi-gradient echo MR thermometry for monitoring of the near-field area during MR-guided high intensity focused ultrasound heating. (7th October 2015) - Lam, Mie K; de Greef, Martijn; Bouwman, Job G; Moonen, Chrit T W; Viergever, Max A; Bartels, Lambertus W
Abstract The multi-gradient echo MR thermometry (MGE MRT) method is proposed to use at the interface of the muscle and fat layers found in the abdominal wall, to monitor MR-HIFU heating. As MGE MRT uses fat as a reference, it is field-drift corrected. Relative temperature maps were reconstructed by subtracting absolute temperature maps. Because the absolute temperature maps are reconstructed of individual scans, MGE MRT provides the flexibility of interleaved mapping of temperature changes between two arbitrary time points. The method's performance was assessed in an ex vivo water bath experiment. An ex vivo HIFU experiment was performed to show the method's ability to monitor heating of consecutive HIFU sonications and to estimate cooling time constants, in the presence of field drift. The interleaved use between scans of a clinical protocol was demonstrated in vivo in a patient during a clinical uterine fibroid treatment. The relative temperature measurements were accurate (mean absolute error 0.3 °C) and provided excellent visualization of the heating of consecutive HIFU sonications. Maps were reconstructed of estimated cooling time constants and mean ROI values could be well explained by the applied heating pattern. Heating upon HIFU sonication and subsequent cooling could be observed in the in vivo demonstration.